2020
DOI: 10.21203/rs.2.21036/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Questionnaire on the breastfeeding and the donation of 70 mothers\donors.

Abstract: INTRODUCTION In feeding premature babies, the first choice is the fresh milk from mother and if this is not possible, the donated milk from the HMBs. The support to the donation of the human milk have proved to be an efficient method of promotion to the breastfeeding. OBJECT The aim is to know the motivations and the experience of the donation to draw lessons for the improvement of our activity about the promotion of breastfeeding and the donation of the milk. MATERIAL AND METHODS 70 donors have been recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…For example, preterm babies < 28 weeks GA had a 2.9 times greater risk of exclusive breastfeeding failure [53]. In our previous publication [86] focused on the amount of donated milk, the data analysis revealed that the maternal age, profession of the donors, and birth weight of their children had a statistically significant impact on the Donor Milk (DM) volume, while the gestational age of the donors' children influenced the milk donation volume; however, this lacked statistical validity.…”
Section: Non-modifiable Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, preterm babies < 28 weeks GA had a 2.9 times greater risk of exclusive breastfeeding failure [53]. In our previous publication [86] focused on the amount of donated milk, the data analysis revealed that the maternal age, profession of the donors, and birth weight of their children had a statistically significant impact on the Donor Milk (DM) volume, while the gestational age of the donors' children influenced the milk donation volume; however, this lacked statistical validity.…”
Section: Non-modifiable Factorsmentioning
confidence: 94%
“…Research also reports that mothers with insufficient breastfeeding in the NICU experience many more breastfeeding-related challenges after discharge [110][111][112]. For this reason, all methods that have proven their effectiveness in promoting breastfeeding initiation in the NICU should be recognized, enhanced and standardized [86,113].…”
Section: Modifiable Factorsmentioning
confidence: 99%
See 1 more Smart Citation